China’s Economic Cyber Espionage Toward the United States as a National Security Threat - Harryanto Aryodiguno; Yohana Novencia Havisaputra (Lampung Center for Global Studies (LCGS), 2023)
Technological developments in the realm of cyberspace have triggered the emergence of new challenges in the form of economic cyber espionage involving the theft of trade secrets and intellectual property which pose a threat to national security. This problem started to receive special attention after the report of economic cyber espionage crimes committed by China against domestic American companies in 2010. In dealing with issues that threaten the country's national security, the United States government has decided to implement a strategy, one of which prioritizes the use of diplomacy. With the cooperation conducted by the United States government, the number of economic cyber espionage cases can finally decrease, and this shows that the use of cyber diplomacy can be the best step to deal with cases of crime in cyberspace. Furthermore, the effectiveness of the strategy adopted by the United States in dealing with the threat of economic cyber espionage from China, especially in 2010 to 2015, will be analyzed more deeply by using the concept of cyber diplomacy through secondary data collection methods.